2016
DOI: 10.5812/ijpbs.4507
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Psychological Capital in Psychological Well-Being and Job Burnout of High Schools Principals in Saveh, Iran

Abstract: Background: Job burnout is the main problem that a large number of organizations are facing and pertains to various factors. Psychological capital is among the main factors affecting individuals' Psychological well-being and job burnout. Objectives: The present study aimed to explore the correlation between psychological capital and psychological well-being with job burnout of the management staff of high schools in Saveh, Iran, in 2015. Materials and Methods: It was a descriptive-correlative study. Statistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 21 publications
0
6
0
1
Order By: Relevance
“…At the same time, as was the case with previous studies, other sociodemographic variables were not significant in the explanation of psychological capital (Arum and Wustari, 2010 ; Caza et al, 2010 ), burnout (Lovell and Wetherell, 2016 ; Manzano-García and Ayala, 2017 ) or PWB (Benjak, 2011 ). Malekitabar et al ( 2017 ) showed that gender does not have a moderating role in the relationship between psychological capital and burnout, nor in the relationship between PWB and burnout. Nevertheless, it is necessary to continue researching the possible moderating role played by sociodemographic variables in explaining psychological capital, burnout and PWB, and the relationship between them, since the results are currently inconclusive (Evans and Steptoe, 2002 ; Maslach and Leiter, 2008 ; Ding et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, as was the case with previous studies, other sociodemographic variables were not significant in the explanation of psychological capital (Arum and Wustari, 2010 ; Caza et al, 2010 ), burnout (Lovell and Wetherell, 2016 ; Manzano-García and Ayala, 2017 ) or PWB (Benjak, 2011 ). Malekitabar et al ( 2017 ) showed that gender does not have a moderating role in the relationship between psychological capital and burnout, nor in the relationship between PWB and burnout. Nevertheless, it is necessary to continue researching the possible moderating role played by sociodemographic variables in explaining psychological capital, burnout and PWB, and the relationship between them, since the results are currently inconclusive (Evans and Steptoe, 2002 ; Maslach and Leiter, 2008 ; Ding et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…One study was removed as it employed a student rather than a workplace sample (Gooty et al, 2009), and four studies were removed due to measuring similar but different constructs from the focus of this study (e.g., measuring career satisfaction) (Ganotice et al, 2016; Guo et al, 2012; Polatci & Akdogan, 2014; Zhang et al, 2014). One further study was also removed due to inconsistent reporting of the correlation coefficients for the relationship between PsyCap and burnout (Malekitabar et al, 2017). Finally, 16 theses were removed due to not having access to the full-text and a further 12 studies were excluded as these studies did not provide the results of the correlation coefficients, despite follow up email requests to the corresponding authors of these studies.…”
Section: Methodsmentioning
confidence: 99%
“…Fostering PsyCap leads to lower burnout and revitalizes the PWB of employees (Manzano-García & Ayala, 2017). However, gender does not play a moderating role in the relationship between PWB and job burnout, and in the relationship between PsyCap and job burnout (Malekitabar et al, 2017). In a sample of nurses, PsyCap was negatively related to emotional exhaustion, and facilitated an in increase in PWB (Laschinger & Grau, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%